Development of innovative hybrid sandwich panel slabs: Advanced numerical simulations and parametric studies - Mastali, Mohammad (2016)
The authors honestly appreciate the collaboration of the following institutions: Civitest for developing DHCC materials and PIEP for conducting VARTM process.